2005
DOI: 10.1681/asn.2004100871
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Chemokine Receptor 1 Blockade Prolongs Survival in Collagen 4A3–Deficient Mice with Alport Disease

Abstract: Human Alport disease is caused by a lack of the ␣3-, 4-, or 5-chain of type IV collagen (COL4A). Affected humans and COL4A3-deficient mice develop glomerulosclerosis and progressive renal fibrosis in the presence of interstitial macrophages, but their contribution to disease progression is under debate. This question was addressed by treating COL4A3-deficient mice with BX471, an antagonist of chemokine receptor 1 (CCR1) that is known to block interstitial leukocyte recruitment. Treatment with BX471 from weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 26 publications
0
84
0
1
Order By: Relevance
“…These results are consistent with a Ccr1-dependent homing of leukocytes from the blood to the kidney. In line with this, in vitro and in vivo studies have reported a role for Ccr1 in T cell and mononuclear phagocyte adhesion and transendothelial migration (14,17,18,27,42,43). Thus, BL5923-induced inhibition of renal T cell and macrophage infiltration could be related to reduced Ccr1-mediated adhesion of leukocytes to activated peritubular capillaries.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These results are consistent with a Ccr1-dependent homing of leukocytes from the blood to the kidney. In line with this, in vitro and in vivo studies have reported a role for Ccr1 in T cell and mononuclear phagocyte adhesion and transendothelial migration (14,17,18,27,42,43). Thus, BL5923-induced inhibition of renal T cell and macrophage infiltration could be related to reduced Ccr1-mediated adhesion of leukocytes to activated peritubular capillaries.…”
Section: Discussionmentioning
confidence: 59%
“…The use of Ccr1-deficient mice or small-molecule Ccr1 antagonists efficiently reduced interstitial infiltration of T cells, mononuclear phagocytes, and/or neutrophils in different mouse models of nephropathy (13,14,17,18,23,27,28,43). In particular, s.c. injections of the Ccr1 antagonist BX471 in MRL-Fas(lpr) mice led to reduced numbers of macrophages, T cells, and Ki-67 positive proliferating cells and reduced fibrosis in the interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrogenic T-cell response and T-cell infiltration in interstitial nephritis initiate, amplify, and perpetuate local inflammatory response which contributes to tubular atrophy and interstitial fibrosis. 34,[36][37][38] However, the emergence of tubular interstitial fibrosis in our a3/Rag-1 DKO mice, as suggested by Ninichuk et al, 32 could result from macrophage recruitment and activation via MCP-1 expression. [33][34][35] Lower serum creatinine levels in the double null mice indicate that ablating active lymphocytes decreases the injury to the renal interstitium.…”
Section: Lymphocytes and Tissue Fibrosis Vs Lebleu Et Almentioning
confidence: 98%
“…39 Purity of isolated cells was verified by flow cytometry. Separated cells were labeled with PKH26 (red fluorescent cell linker kit; Sigma-Aldrich Chemicals, Steinheim, Germany) and labeling efficacy was assessed by flow cytometry.…”
Section: In Vivo Assay Of Renal Macrophage Recruitmentmentioning
confidence: 99%